Study of serum ferritin levels in various phases of dengue in pediatric dengue patients admitted in a tertiary hospital - N, Meghana; N, Pradeep (Indian Journal of Child Health, 2024)
Background: Dengue is a cause of public health concern with case fatality rate of 1%. Ferritin is an acute-phase reactant which is produced in response to infection and inflammation. The aim of this study is to evaluate serum ferritin levels in various phases of dengue in pediatric dengue patients. Methods: A hospital-based, prospective, and observational study was done involving 30 dengue cases diagnosed by positive NS1 antigen or dengue specific serology (capture enzyme-linked immunosorbent assay). Serum ferritin was estimated by electrochemiluminescence in all three phases of dengue. Clinical and platelet count monitoring was done daily; respectively. All children classified as dengue with or without warning signs and severe dengue according to the World Health Organization guidelines on diagnosis treatment, prevention, and control of dengue, 2009. Results: Out of total of 30 children with mean age of the children were 7 years, and 61% were male who were majority. High serum ferritin levels were noted during critical phase. Eight children with dengue shock syndrome and one with acute respiratory distress syndrome were managed in intensive care unit as compared to non-severe dengue with statistically significant difference as p